Nickel-based alloy composite powder and preparation method and application thereof
By adding MoC powder to nickel-based alloys to form grain boundary film-like carbides, the crack problem in nickel-based high-temperature alloy additive manufacturing is solved, the density and performance of the material are improved, and it is suitable for aerospace with high temperature and fatigue performance requirements. and maintain the applicability of the batch production of alloys.
Patent Information
- Application Number
- CN202411526014.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-30
AI Technical Summary
In the process of additive manufacturing of nickel-based high-temperature alloys, metallurgical defects such as cracks are prone to occur, which affects its high temperature and fatigue properties and hinders its engineering application in the aerospace field.
By mixing and adding the C elements and Mo elements in the nickel-based alloy in the form of MoC powder, a continuous film-like M23C6 carbide at the grain boundary is formed to fill the grain boundary, eliminate cracks, and no other new elements are introduced to keep the alloy components in Within the original range.
It effectively eliminates the forming cracks of nickel-based high-temperature alloys, improves the density and mechanical properties of the material, is suitable for aerospace applications with high temperature and fatigue performance requirements, and is suitable for rapid batch production.
Smart Images

Figure CN119319243A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of additive manufacturing, and in particular to a nickel-based alloy composite powder for eliminating cracks in nickel-based alloy additive manufacturing, and a preparation method and application thereof. Background Art
[0002] The demand for additively manufactured high-temperature alloy components in major projects such as aero-engines, hypersonic vehicles, and heavy-load rockets is becoming more and more urgent. Currently, the nickel-based high-temperature alloys that have been realized or are close to engineering applications are still mainly traditional cast and forged alloy grades such as GH3536, GH3625, and GH4169. Most of these alloys have good weldability and good additive processability, but their high-temperature performance is limited and cannot meet the needs of future high-generation aerospace power applications. High-temperature alloys with higher temperature bearing capacity and higher performance, such as GH3230, IN738 (K438), and CM247LC (K447), are affected by high solid solution alloying and γ′ phase content. Under the influence of rapid solidification and large thermal gradients in the additive process, cracks and other metallurgical defects will generally appear in the formed specimens. These defects will further affect the mechanical properties of the specimens and components, especially the high-temperature durability and fatigue properties of the alloy, which has an important impact on the engineering application of such alloys.
[0003] Based on current application needs, exploring the applicability of additive manufacturing of high-temperature alloys with higher alloying and higher performance, and preparing high-density, crack-free high-temperature alloy components through material design optimization has become an important research direction. The existing technology mainly suppresses forming cracks by adjusting the alloy composition, by adding other elements to the alloy or changing the composition ratio of the elements, but this method usually introduces other elements into the alloy or changes the initial composition range of the alloy, affecting the batch application of the alloy.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a nickel-based alloy composite powder for eliminating cracks in nickel-based alloy additive manufacturing, and a preparation method and application thereof.
[0006] Specifically, the technical solution of the present invention is as follows: In a first aspect, the present invention provides a nickel-based alloy composite powder, which consists of a basic powder and a functional powder; the basic powder is a nickel-based alloy GH3230 powder with a particle size of 15-150 μm; the functional powder is a MoC compound powder with a particle size of 0.05-5 μm, or a mixed powder composed of a C single element powder and a Mo single element powder; the addition amount of the functional powder in the nickel-based alloy composite powder is 0.5%~3%.
[0007] The nickel-based alloy powder provided by the present invention has the function of eliminating cracks in the manufacturing of nickel-based alloy additives. Specifically, part of the C element and the Mo element in the nickel-based alloy are mixed and added in the form of additional small-particle powder (such as MoC powder). In the process of additive manufacturing, more M23C6 carbides are formed in a continuous film-like distribution at the grain boundary, which fills the grain boundary, eliminates the forming cracks of the nickel-based high-temperature alloy, and improves the forming density of the material. At the same time, the present invention only changes the existing form of the C element and the Mo element in the powder, and does not introduce other new elements into the nickel-based alloy. After mixing, the composition range of the total C element and the Mo element can be controlled within the original range, which is conducive to the rapid batch application of the product.
[0008] Preferably, the nickel-based alloy GH3230 powder includes the following components in percentage by mass: C: 0.05%~0.15%; Cr: 20.00%~24.00%; Co: ≤5.00%; W: 13.00%~15.00%; Mo: 1.00%~3.00%; Al: 0.20%~0.50%; Ti: ≤0.10%; Fe: ≤3.00%; B: ≤0.015%; Si: 0.25%~0.75%; Mn: 0.30%~1.00%; La: 0.005%-0.05%; the balance is Ni.
[0009] Preferably, in the nickel-based alloy composite powder, the total mass percentage of C element does not exceed 0.15%; the total mass percentage of Mo element does not exceed 3.00%.
[0010] Further preferably, the functional powder is MoC compound powder; the MoC powder is uniformly coated on the surface of the nickel-based alloy GH3230 powder by mixing.
[0011] More preferably, the particle size of the MoC compound powder is 50±10 nm; and the particle size of the nickel-based alloy GH3230 powder is 15-53 μm.
[0012] In a second aspect, the present invention provides a method for preparing the nickel-based alloy composite powder, which comprises the step of mixing a basic powder and a functional powder, wherein the mixing speed is 20±5 rpm / min and the mixing time is 6±3 h.
[0013] In a third aspect, the present invention provides a nickel-based alloy obtained by additive manufacturing of the nickel-based alloy composite powder described above.
[0014] Preferably, the additive manufacturing method is laser selective melting, directed energy deposition or electron beam melting.
[0015] Further preferably, the additive manufacturing method is laser selective melting; wherein the laser power is 100-300 W, the scanning speed is 600-1200 mm / s, the scanning spacing is 0.09-0.12 μm, and the powder layer thickness is 30-80 μm.
[0016] The nickel-based alloy provided by the present invention is filled with M23C6 type carbides with continuous film distribution (rather than point distribution) at its grain boundaries, which can eliminate the forming cracks of the nickel-based high-temperature alloy and improve the forming density of the material.
[0017] Beneficial effects: The present invention provides a nickel-based alloy composite powder and a preparation method and application thereof. The nickel-based alloy composite powder is obtained by mixing nickel-based alloy GH3230 powder with a base particle size of 15-150 μm and functional powder containing Mo and C elements with a particle size of 0.05-5 μm in proportion. The nickel-based alloy composite powder provided by the present invention has the function of eliminating cracks in nickel-based alloy material manufacturing; and no other new elements are introduced into the nickel-based alloy, which is conducive to the rapid batch application of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be described below.
[0019] Figure 1 This is the morphology of GH3230 powder mixed with 1% MoC powder in Example 1.
[0020] Figure 2 This is the metallographic structure of GH3230+1%MoC in Example 1.
[0021] Figure 3 This is the morphological microstructure of GH3230+1%MoC in Example 1 (the white one is M23C6 carbide).
[0022] Figure 4 This is the metallographic structure of GH3230+1.5%MoC in Example 2.
[0023] Figure 5 This is the metallographic structure of GH3230+1.5%MoC in Example 3.
[0024] Figure 6 This is the morphological metallographic structure of the GH3230 alloy formed by laser selective melting in Comparative Example 1.
[0025] Figure 7 This is the morphological microstructure of GH3230 in Comparative Example 1 (the white one is M23C6 carbide).
[0026] Figure 8This is the morphological metallographic structure of the GH3230 alloy formed by laser selective melting in Comparative Example 2. DETAILED DESCRIPTION
[0027] The present invention provides a nickel-based alloy composite powder and a preparation method and application thereof. The nickel-based alloy composite powder can control the distribution morphology of cracking elements C and Mo in the nickel-based alloy, and in the process of material additive manufacturing, more M23C6 carbides are formed to be distributed in a continuous film at the grain boundary, thereby filling the grain boundary, eliminating the forming cracks of the nickel-based high-temperature alloy, and improving the forming density of the material.
[0028] Specifically, the present invention provides a nickel-based alloy composite powder for eliminating cracks in nickel-based alloy additive manufacturing, which uses nickel-based alloy powder A as a raw material, and functional powder containing Mo and C elements is mixed into the nickel-based alloy powder A (part of the C and Mo elements in the nickel-based alloy are mixed into the raw material powder in the form of functional powder).
[0029] The nickel-based alloy composite powder provided by the present invention can be formed by additive manufacturing technology.
[0030] In the present invention, the element composition of the nickel-based alloy powder A, in terms of mass percentage, includes: C: 0.05%~0.15%; Cr: 20.00%~24.00%; Co: ≤5.00%; W: 13.00%~15.00%; Mo: 1.00%~3.00%; Al: 0.20%~0.50%; Ti: ≤0.10%; Fe: ≤3.00%; B: ≤0.015%; Si: 0.25%~0.75%; Mn: 0.30%~1.00%; La: 0.005%-0.05%; and the balance is Ni.
[0031] In the present invention, the mixed Mo element and C element are added in the form of single element powder or in the form of MoC compound powder.
[0032] In the present invention, the functional powder is preferably mixed in the form of MoC compound powder, and the added mass fraction of the MoC powder is 0.5% to 3%.
[0033] In the nickel-based alloy composite powder for eliminating nickel-based alloy additive manufacturing cracks provided by the present invention, after the Mo element and the C element are completely mixed, the total mass percentage of the C element and the Mo element does not exceed the upper limit of the content of each element in the nickel-based alloy powder A of 0.15% and 3%, respectively.
[0034] In the present invention, the preparation process of the nickel-based alloy powder A includes but is not limited to vacuum gas atomization, electrode induction gas atomization, plasma rotating electrode method, etc., and the morphology of the powder is spherical or nearly spherical.
[0035] In the present invention, the mixing method of the Mo and C element powders into the nickel-based alloy powder A includes but is not limited to ball milling mixing, V-type mixing, three-dimensional mixing, resonance mixing, etc.
[0036] In the present invention, the MoC powder is uniformly coated on the surface of the nickel-based alloy powder A. The particle size of the nickel-based alloy powder A is in the range of 15 μm-150 μm, and the particle size of the MoC powder is in the range of 0.05 μm-5 μm.
[0037] The present invention forms a crack-free alloy by means of an additive manufacturing technology, wherein the additive manufacturing technology is one of laser selective melting, directed energy deposition or electron beam melting forming processes.
[0038] As a more preferred embodiment, for laser selective melting, the laser power is 100-300W, the scanning speed is 600-1200mm / s, the scanning interval is 0.09-0.12μm, the powder layer thickness is 30-80μm, and the laser scanning strategy is linear scanning or chessboard scanning.
[0039] The present invention mixes MoC powder in nickel-based alloy powder, and combines the characteristics of small melting area and fast solidification rate of additive manufacturing technology such as laser selective melting, so that more M23C6 carbides in the formed nickel-based alloy are precipitated along the grain boundary, fill the solidification cracks, significantly reduce the forming cracks of the nickel-based alloy, and improve the forming density. The nickel-based alloy powder for eliminating the manufacturing cracks of nickel-based alloy additives proposed by the present invention is that part of the C element and the Mo element in the nickel-based alloy are mixed and added in the form of MoC powder, which only changes the existence form of the C element and the Mo element in the powder, and does not introduce other new elements into the nickel-based alloy. After mixing, the composition range of the total C element and the Mo element can be controlled within the original range, which is conducive to improving the rapid batch application of the method.
[0040] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] The endpoints and any values of the ranges disclosed in this specification are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0042] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "specific implementations", or "some specific implementations" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiment of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0043] In the examples provided in this specification, if no specific techniques or conditions are specified, the techniques or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.
[0044] Embodiment 1: (1) The nickel-based alloy used in this embodiment is GH3230 alloy, and the composition percentage by mass of the alloy is: C: 0.06; Cr: 22.3; Co: 2.0; W: 13.5; Mo: 1.8; Al: 0.4; Ti: 0.08; Fe: 1.6; B: 0.005; Si: 0.42; Mn: 0.50; La: 0.009.
[0045] (2) A GH3230 powder having the composition described in (1) was prepared by a vacuum gas atomization process, and coarse particles and ultrafine particles in the powder were removed by screening and airflow classification processes to obtain a GH3230 powder with a particle size of 15-53 μm.
[0046] (3) Powder mixing: Add 50nm MoC powder to GH3230 powder, and the addition ratio of MoC powder is 1%. Use a three-dimensional mixer to fully mix the 15-53μm GH3230 powder and MoC powder. The speed of the three-dimensional mixer is 20rpm / min, and the mixing time is 6h.
[0047] The morphology of the powder after mixing is Figure 1 shown.
[0048] (4) The evenly mixed powder is added into the laser selective melting equipment. The forming size of the equipment is 125mm*125mm*125mm. Stainless steel is selected as the forming substrate. The substrate is installed on the forming platform. The substrate is heated to 200°C for insulation. High-purity argon gas with a purity of 99.99wt.% is introduced to provide gas protection for the equipment. When the oxygen content is lower than 10ppm, the laser is turned on for forming. The forming process parameters are: laser power: 180W, scanning speed: 800mm / s, scanning spacing: 0.09mm, scanning layer thickness: 0.03mm, and the scanning strategy is linear scanning.
[0049] (5) The obtained GH3230 alloy samples were subjected to forming crack analysis. The metallographic results are as follows: Figure 2 As shown. Figure 2 It can be seen that there are only a small amount of pores in the as-formed specimen, and no cracks are observed. The distribution of grain boundary carbides is shown in Figure 3 As shown, it can be seen that more M23C6 carbides are distributed in the form of films at the grain boundaries, filling the cracks and inhibiting the occurrence of cracks.
[0050] Embodiment 2: (1) The nickel-based alloy used in this embodiment is GH3230 alloy, and the composition percentage by mass of the alloy is: C: 0.05; Cr: 22.3; Co: 2.0; W: 13.5; Mo: 1.5; Al: 0.4; Ti: 0.08; Fe: 1.6; B: 0.005; Si: 0.42; Mn: 0.50; La: 0.009.
[0051] (2) A GH3230 powder having the composition described in (1) was prepared by a vacuum gas atomization process, and coarse particles and ultrafine particles in the powder were removed by screening and airflow classification processes to obtain a GH3230 powder with a particle size of 15-53 μm.
[0052] (3) Powder mixing: Add 50nm MoC powder to GH3230 powder, and the addition ratio of MoC powder is 1.5%. Use a three-dimensional mixer to fully mix 15-53μm GH3230 powder and MoC powder, where the speed of the three-dimensional mixer is 20rpm / min and the mixing time is 6h.
[0053] (4) The evenly mixed powder is added into the laser selective melting equipment. The forming size of the equipment is 125mm*125mm*125mm. Stainless steel is selected as the forming substrate. The substrate is installed on the forming platform. The substrate is heated to 200°C for insulation. High-purity argon gas with a purity of 99.99wt.% is introduced to provide gas protection for the equipment. When the oxygen content is lower than 10ppm, the laser is turned on for forming. The forming process parameters are: laser power: 180W, scanning speed: 800mm / s, scanning spacing: 0.09mm, scanning layer thickness: 0.03mm, and the scanning strategy is linear scanning.
[0054] (5) The obtained GH3230 alloy samples were subjected to forming crack analysis. The metallographic results are as follows: Figure 4 The results show that no cracks were observed in the as-formed specimens. M23C6 carbides were distributed in the form of films at the grain boundaries, filling the cracks and inhibiting their generation.
[0055] Embodiment 3: (1) The nickel-based alloy used in this embodiment is GH3230 alloy, and the composition percentage by mass of the alloy is: C: 0.05; Cr: 22.3; Co: 2.0; W: 13.5; Mo: 1.5; Al: 0.4; Ti: 0.08; Fe: 1.6; B: 0.005; Si: 0.42; Mn: 0.50; La: 0.009.
[0056] (2) A GH3230 powder having the composition described in (1) was prepared by a vacuum gas atomization process, and coarse particles and ultrafine particles in the powder were removed by screening and airflow classification processes to obtain a GH3230 powder with a particle size of 15-53 μm.
[0057] (3) Powder mixing: Add 50nm MoC powder to GH3230 powder, and the addition ratio of MoC powder is 1.5%. Use a three-dimensional mixer to fully mix 15-53μm GH3230 powder and MoC powder, where the speed of the three-dimensional mixer is 20rpm / min and the mixing time is 6h.
[0058] (4) The evenly mixed powder is added into the laser selective melting equipment. The forming size of the equipment is 125mm*125mm*125mm. Stainless steel is selected as the forming substrate. The substrate is installed on the forming platform. The substrate is heated to 200°C for insulation. High-purity argon gas with a purity of 99.99wt.% is introduced to provide gas protection for the equipment. When the oxygen content is lower than 10ppm, the laser is turned on for forming. The forming process parameters are: laser power: 220W, scanning speed: 900mm / s, scanning spacing: 0.09mm, scanning layer thickness: 0.03mm, and the scanning strategy is linear scanning.
[0059] (5) The obtained GH3230 alloy samples were subjected to forming crack analysis. The metallographic results are as follows: Figure 5 The results show that no cracks were observed in the as-formed specimens. M23C6 carbides were distributed in the form of films at the grain boundaries, filling the cracks and inhibiting their generation.
[0060] Comparative Example 1: (1) The nickel-based alloy used in this comparative example is GH3230 alloy, and the composition percentage by mass of the alloy is: C: 0.06; Cr: 22.3; Co: 2.0; W: 13.5; Mo: 1.8; Al: 0.4; Ti: 0.08; Fe: 1.6; B: 0.005; Si: 0.42; Mn: 0.50; La: 0.009.
[0061] (2) A GH3230 powder having the composition described in (1) was prepared by a vacuum gas atomization process, and coarse particles and ultrafine particles in the powder were removed by screening and airflow classification processes to obtain a GH3230 powder with a particle size of 15-53 μm.
[0062] (3) MoC powder is not added to the powder.
[0063] (4) The obtained GH3230 powder was added to the laser selective melting equipment with a forming size of 125 mm*125 mm*125 mm. Stainless steel was selected as the forming substrate and the substrate was installed on the forming platform. The substrate was heated to 200 °C for insulation and high-purity argon gas with a purity of 99.99 wt.% was introduced to provide gas protection for the equipment. When the oxygen content was lower than 10 ppm, the laser was turned on for forming. The forming process parameters were: laser power: 180 W, scanning speed: 800 mm / s, scanning spacing: 0.09 mm, scanning layer thickness: 0.03 mm, and the scanning strategy was linear scanning.
[0064] (5) The obtained GH3230 alloy samples were subjected to forming crack analysis. The metallographic results are as follows: Figure 6 As shown, from Figure 6 It can be seen that cracks are observed in the shaped specimen. The distribution of grain boundary carbides is as follows Figure 7 As shown, it can be seen that only a small amount of M23C6 carbides are distributed in the form of dots at the grain boundaries and cannot play a filling and inhibiting role in cracks.
[0065] Comparative Example 2: (1) The nickel-based alloy used in this comparative example is GH3230 alloy, and the composition percentage by mass of the alloy is: C: 0.11; Cr: 22.3; Co: 2.0; W: 13.5; Mo: 2.5; Al: 0.4; Ti: 0.08; Fe: 1.6; B: 0.005; Si: 0.42; Mn: 0.50; La: 0.009.
[0066] (2) A GH3230 powder having the composition described in (1) was prepared by a vacuum gas atomization process, and coarse particles and ultrafine particles in the powder were removed by screening and airflow classification processes to obtain a GH3230 powder with a particle size of 15-53 μm.
[0067] (3) MoC powder is not added to the powder.
[0068] (4) The obtained GH3230 powder was added to the laser selective melting equipment with a forming size of 125 mm*125 mm*125 mm. Stainless steel was selected as the forming substrate and the substrate was installed on the forming platform. The substrate was heated to 200 °C for insulation and high-purity argon gas with a purity of 99.99 wt.% was introduced to provide gas protection for the equipment. When the oxygen content was lower than 10 ppm, the laser was turned on for forming. The forming process parameters were: laser power: 220 W, scanning speed: 900 mm / s, scanning spacing: 0.09 mm, scanning layer thickness: 0.03 mm, and the scanning strategy was linear scanning.
[0069] (5) The obtained GH3230 alloy samples were subjected to forming crack analysis. The metallographic results are as follows: Figure 8 As shown, from Figure 8 It can be seen that cracks are observed in the formed specimens.
[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. Nickel-based alloy composite powder, characterized in that: It is composed of basic powder and functional powder; the basic powder is nickel-based alloy GH3230 powder with a particle size of 15-150μm; the functional powder is MoC compound powder with a particle size of 0.05-5μm, or a mixed powder composed of C single element powder and Mo single element powder; the addition amount of the functional powder in the nickel-based alloy composite powder is 0.5%~3%.
2. The nickel-based alloy composite powder according to claim 1, characterized in that: The nickel-based alloy GH3230 powder includes the following components in percentage by mass: C: 0.05% to 0.15%; Cr: 20.00% to 24.00%; Co: ≤5.00%; W: 13.00% to 15.00%; Mo: 1.00% to 3.00%; Al: 0.20% to 0.50%; Ti: ≤0.10%; Fe: ≤3.00%; B: ≤0.015%; Si: 0.25%~0.75%; Mn: 0.30%~1.00%; La: 0.005%-0.05%; the balance is Ni.
3. The nickel-based alloy composite powder according to claim 1 or 2, characterized in that: In the nickel-based alloy composite powder, the total mass percentage of C element does not exceed 0.15%; the total mass percentage of Mo element does not exceed 3.00%.
4. The nickel-based alloy composite powder according to any one of claims 1 to 3, characterized in that: The functional powder is MoC compound powder; the MoC powder is evenly coated on the surface of the nickel-based alloy GH3230 powder by mixing.
5. The nickel-based alloy composite powder according to claim 4, characterized in that: The particle size of the MoC compound powder is 50±10 nm; the particle size of the nickel-based alloy GH3230 powder is 15-53 μm.
6. The method for preparing the nickel-based alloy composite powder according to any one of claims 1 to 5, characterized in that: The basic powder and the functional powder are mixed at a rotation speed of 20±5 rpm / min for 6±3 h.
7. Nickel-based alloy, characterized in that The nickel-based alloy composite powder is obtained by additive manufacturing according to any one of claims 1 to 5.
8. The nickel-based alloy according to claim 7, characterized in that: The additive manufacturing method is laser selective melting, directed energy deposition or electron beam melting.
9. The nickel-based alloy according to claim 8, characterized in that: The additive manufacturing method is laser selective melting, wherein the laser power is 100-300W, the scanning speed is 600-1200mm / s, the scanning spacing is 0.09-0.12μm, and the powder layer thickness is 30-80μm.
10. The nickel-based alloy according to any one of claims 7 to 9, characterized in that: The grain boundaries are filled with continuous film-like distribution of M23C6 type carbides.
Citation Information
Patent Citations
Preparation method and application of anti-crack nickel-based superalloy powder
CN116618666A
Nickel-based superalloy composite powder for 3D printing
CN117684068A
The scalar vector data from the memory in a memory system designed for prefetching method
JP1992505225A
Method for producing metal-ceramic powder composition
RU2644834C1